Implementation of Cyberspace Cooperation between Indonesia and United States A Combating Cyberterrorism in Indonesia, 2019–2023 - Khoirunnisa; Silvi, Minar; Surya, Evelin Angelina Rizqi (Ilomata International Journal of Social Science, 2024)
This research focuses on the implementation of cyberspace cooperation between Indonesia and the United States in an effort to tackle cyber terrorism in Indonesia in the 2019-2023 period. The background of this research is based on the increasing cyber threats faced by Indonesia, including attacks on critical infrastructure and government data. This research uses a qualitative method with a literature study approach to collect and analyze data from various sources such as documents, books, journal articles, reports related to the problem to be solved, and publications related to cyber security and cyber diplomacy. The results show that cooperation between Indonesia and the United States has strengthened Indonesia's cyber defense capabilities through various initiatives, including incident management capacity building, national cyber strategy development, and information exchange. This cooperation is also supported by global cybersecurity policies and initiatives that involve both countries in international forums such as the ASEAN-US Cyber Policy Dialogue. This research concludes that cyberspace cooperation between Indonesia and the United States is a strategic step to address cyber threats and enhance security stability in the Southeast Asian region. Policy recommendations include further developing the cooperation framework and increasing cybersecurity awareness among the public.